Formulation And Evaluation of Pergularia Daemia Ointment by Leaf Extract - Firoz, Syed Gouse; Kumar, A. Arun; Rani, K. Sudha; Padma, A.Venkata; Brahmini, M. Ramya; Mohan, S. Jagan; Adilakshmi, N. (Journal of Neonatal Surgery, 2025)
The study formulates and evaluates an herbal ointment using Pergularia daemia leaf extract for wound healing and antimicrobial use. The extract contains flavonoids, alkaloids, and tannins, enhancing therapeutic effects. Results show strong antimicrobial action, wound contraction, and epithelization, supporting its potential as a natural alternative. Clinical trials are needed for further validation